The in-laws - Morris, John 1926-2018 (<<The>> Criterion collection, 2016)
"On the eve of their children's marriage, NYC in-laws Sheldon Kornpett and Vince Ricardo embark on a series of misadventures involving the CIA, the Treasury Department and Central American dictators." [imdb.com]
Original: USA 1979
Bildformat 1.85:1
DVD special edition features: new 2K digital restoration ; audio commentary from 2003 featuring director Arthur Hiller, actors Alan Arkin and Peter Falk, and writer Andrew Bergman ; new interview with Arkin ; In support of "The in-laws," a new interview program featuring actors Ed Begley Jr., Nancy Dussault, James Hong, and David Paymer ; trailer ; plus: a booklet featuring an essay by comedy writer Stephen Winer and a 2011 recollection of the making of the film by Hiller
Keywords: Film; DVD-Video